AC-Treuhand: Substantial Fines for Facilitators of Cartels. (18th January 2016) - Vallery, Anne; Schell, Caroline
Abstract: In a judgment issued on 22 October 2015, the Court of Justice of the European Union (CJEU) dismissed the appeal brought by a consultancy agency against the judgment of the General Court confirming its participation in a cartel as facilitator and its consequent infringement of Article 101 Treaty on the Functionning of the European Union (TFEU) and affirmed a broad interpretation of the scope of this provision.